Voluntary sport programs for individuals with mental health disorders: The trainer's and participant's view - Florence Epiney; Carina Baumberger; Carole Pauli; Daniela Loosli; Hansjörg Znoj; Birgit Kleim; Frank Wieber; Nikolai Kiselev (Bern Open Publishing, 2024)
Introduction There is strong evidence that physical activities are important in increasing and maintaining mental health as well as in preventing relapse after mental health disorders (Schulz et al., 2011). Physical activity is an integral part of the treatment program in psychiatric hospitals in Switzerland (CH; Brand et al., 2016). However, after discharge from the hospital in CH, there are insufficient opportunities to engage in physical activity for individuals with mental health disorders (IMHD). To close this gap, voluntary sports groups (VSG) for IMHD have been growing in Switzerland since 2016, mainly organized by the PluSport Umbrella Organization of Swiss Disabled Sports (Kiselev & Loosli, 2019). Yet, little is known about these VSG and their training settings. The perspectives of IMHD and trainers of these groups as well as the perceived barriers and facilitators for participating for IMHD have neither been assessed nor included in the design of sports programs. Therefore, two studies aimed to explore the point of view of the IMHD (first study) and the trainers of these groups (second study) on challenges, barriers, and facilitators for IMHD regarding participation in VSG for IMHD. Additionally, given the crucial role of the trainers in the training process and the importance of their interpersonal characteristics, both studies aimed to identify reasons/motivations and proper personality characteristics of the VSG trainers from the interviewees' perspective. Methods Both studies consisted of 15 semi-structured interviews each (with participants (1st study) and with trainers (2nd study) of VSG for IMHD). The results were analyzed using thematic analysis using Nvivo (Guest et al., 2012). Results Several training facilitators and trainers' characteristics supporting the participation of the IMHD in VSG for IMHD were named by interviewees (e.g., offer-specific, emotional, rational motives, social skills of the trainers, and ability to set boundaries). At the same time, respondents reported several barriers as possible inhibitors for the participation of IMHD in VSG for IMHD (e.g., intrapersonal, structural, offer-specific, interpersonal and socio-cultural). Within the interviews, IMHD described predominantly positive perceived outcomes from participating in VSG for IMHD. On the other side, trainers of VSG for IMHD highlighted the satisfaction of doing sports with IMHD and of the contribution to improving the physical activity habits of IMHD as the main factors for their commitment as coaches (Baumberger et al., under review; Epiney et al., 2023). Discussion/Conclusion IMHD benefit socially, physically, and psychologically from participating in VSG for IMHD. However, participation is associated with barriers that need to be minimized in the future to make participation more accessible. Furthermore, the findings suggest improving the recruitment of future trainers of VSG for IMHD by focusing on assessing the appropriate personality characteristics of trainers and their motives. Additionally, findings should be integrated into the educational materials of Swiss disabled sports systems to ensure the proper upskilling of the new and present trainers of VSG for IMHD and ensure the quality and attractiveness of these groups for the target population . Finally, a large-scale survey is necessary to validate the results among the population. References Baumberger, C., Wieber, F., Pauli, C., Loosli, D., Kleim, B., & Kiselev, N. (under review). Active bodies - Active minds? A deep dive into the voluntary sports programs for individuals with psychiatric disorders in Switzerland: Participants view. BMC Public Health. Brand, S., Colledge, F., Beeler, N., Pühse, U., Kalak, N., Sadeghi Bahmani, D., Mikoteit, T., Holsboer-Trachsler, E., & Gerber, M. (2016). The current state of physical activity and exercise programs in German-speaking, Swiss psychiatric hospitals: Results from a brief online survey. Neuropsychiatric Disease and Treatment, 12, 1309-1317. https://doi.org/10.2147/NDT.S107313 Epiney, F., Wieber, F., Loosli, D., Znoj, H., & Kiselev, N. (2023). Voluntary sports programs for individuals with mental health disorders: The trainer's view. Plos one, 18(10), Article e0290404. https://doi.org/10.1371/journal.pone.0290404 Guest, G., MacQueen, K., & Namey, E. (2012). Applied Thematic Analysis. SAGE. https://doi.org/10.4135/9781483384436 Kiselev, N., & Loosli, D. (2019). Kann ich mitmachen? Behinderten- und Rollstuhlsportclubs in der Schweiz und der Zugang zum Behinderten- und Rollstuhlsport [Disabled and wheelchair sports clubs in Switzerland and access to disabled and wheelchair sports]. Schweizerische Zeitschrift für Heilpädagogik, 25(5-6), 13-20. Schulz, K. H., Meyer, A., & Langguth, N. (2011). Körperliche Aktivität und psychische Gesundheit [Physical activity and mental health]. Bundesgesundheitsblatt - Gesundheitsforschung - Gesundheitsschutz, 55(1), 55-65. https://doi.org/10.1007/s00103-011-1387-x